Restoring the balance: regeneration of hair cells in the vestibular system of the inner ear. Issue 14 (April 2020) - Forge, Andrew; Jagger, Daniel J.; Gale, Jonathan E.
Abstract : Loss of the sensory 'hair cells' (HCs) from the vestibular (balance) system of the inner ear results in dizziness and balance dysfunction contributing to falls. In the inner ears of non-mammalian vertebrates, there is spontaneous and complete replacement of lost HCs. The regenerates derive from the non-sensory supporting cells (SCs) that surround each HC either from the daughter cells following SC division or by direct, non-mitotic conversion of SCs. In mammals, there is a very limited capacity to regenerate vestibular HCs but only a small percentage is replaced. They arise exclusively by SC conversion. Recent work in mice, and some in humans, has shown possibilities for inducing SCs to convert to cells expressing some HC characteristics, but that differentiation to fully functional HCs is incomplete. Work to identifying necessary transcription factors, and/or epigenetic modifiers as well as targets to promote SC proliferation is ongoing.